Syria and Iraq as Proxy Colonies before Colonization: The Ottoman Vali versus the Western Consul in the Era of Capitulations - Haddad, Mahmoud (Die Welt des Islams, 2020)
This study tries to show that European policies influenced not only the Ottoman center at Istanbul in the late nineteenth and early twentieth centuries, but also the workings of the provincial adminstrations as well. Ottoman Syria and Iraq were, according to this assessment, proxy colonies before the direct colonization of post World War I.